Combination of tofacitinib and tacrolimus therapy in refractory interstitial lung disease associated with anti-synthetase syndrome: a case series of six patients - Qiuyu Fan; Wei Huang; Shaohui Song; Huiqin Yang; Ya Liu; Chao Jia; Yu Xiao; Liang Zou (Frontiers in Immunology, 2026)
Objective This study aimed to assess the efficacy and safety of tofacitinib and tacrolimus (TAT) combination therapy for treating refractory interstitial lung disease (ILD) associated with anti-synthetase syndrome (ASyS-ILD). Method Patients with refractory ASyS-ILD who were treated with TAT at Wuhan No. 1 Hospital were included in the study from January 2020 to May 2024. A retrospective analysis of the clinical data from these patients is presented. Result A total of six patients, one male patient and five female patients, primarily presented with refractory ASyS-ILD. All patients experienced symptomatic relief following TAT therapy, which facilitated the successful tapering of glucocorticoids (GCs, 24.67 ± 17.42 vs. 8.34 ± 1.89, p = 0.004). After treatment, PGA, PGA-VAS, PhGA-VAS, and MMT-8 scores significantly improved, and diffusing capacity of carbon monoxide (DLCO) increased in all 6 patients. Moreover, the serum levels of creatine kinase (CK) and lactate dehydrogenase (LDH) were notably reduced, and inflammatory indices, including C-reactive protein (CRP), ferritin, and erythrocyte sedimentation rate (ESR), declined significantly in all patients after administration of TAT. Additionally, peripheral white blood cell and neutrophil counts were significantly reduced, while lymphocyte counts increased, with a markedly decreased neutrophil/lymphocyte ratio in patients with ASyS-ILD receiving treatment. However, during treatment, two patients developed herpes zoster, which resolved with antiviral treatment. Unfortunately, two fatalities occurred, one due to disease progression from severe Aspergillus fumigatus pneumonia and the other due to pancreatic cancer. Conclusion In this series of patients with refractory ASyS-ILD, TAT therapy showed some clinical effectiveness over the short term, with an observed steroid-sparing outcome, suggesting a possible benefit. Nevertheless, larger prospective controlled studies are necessary to further assess its efficacy and safety.